Genome‐wide association analysis for lethal brachycephalic‐like facial dysmorphia in Labrador Retrievers. (5th November 2019) - Vasiliadis, D.; Dierks, C.; Hoffmann, H.; Hellige, M.; Hewicker‐Trautwein, M.; Metzger, J.; Distl, O.
Summary: A GWAS was performed for inborn X‐linked facial dysmorphia with severe growth retardation in Labrador Retrievers. This lethal condition was mapped on the X chromosome at 17–21 Mb and supported by eight SNPs in complete LD. Dams of affected male puppies were heterozygous for the significantly associated SNPs and male affected puppies carried the associated alleles hemizygously. In the near vicinity to the associated region, RPS6KA3 was identified as a candidate gene causing facial dysmorphia in humans and mice known as Coffin–Lowry syndrome. Haplotype analysis showed significant association with the phenotypes of all 18 animals under study. This haplotype was validated through normal male progeny from a dam with the not‐associated haplotype on both X chromosomes but male affected full‐sibs with the associated haplotype.